OPTIMIZATION OF THE ALUMINUM SULFATE AND PAC (POLY ALUMINUM CHLORIDE) COAGULANT ON TELLO RIVER WATER TREATMENT - Setyo Erna Widiyanti (Universitas Lambung Mangkurat, 2018)
Abstract- Tello River water used by PT. PLN SULTANBATARA for sanitation and process water. One of the process's water is boiler feed water. River water has fluctuative characteristics depending on the season that occurs such as turbidity and Total Suspended Solid (TSS). The presence of TSS in boiler feed water needs to be minimized as it can decrease boiler performance in generating heat. The concentration of TSS in river water can be removed by coagulation and flocculation method with the addition of coagulant. Excessive coagulant distribution will increase the concentration of dissolved solids (TDS) of water. Thus, it is necessary to determine the optimum concentration of coagulant based on initial TSS concentration of river water. The objective of this research is to determine the optimum concentration of Aluminum Sulfate (Al2(SO4)3) and PAC (Poly Aluminum Chloride) Coagulant in reducing TSS water of Tello River. The sample used in this research is Tello river water which has an initial TSS concentration of 150 mg/L. The coagulant used was Aluminum Sulfate and PAC with several concentration variation of 5% - 40% to the initial TSS concentration of river water. Analysis of TSS content of samples using Gravimetry method. The optimum concentration of coagulant Aluminum Sulfate and PAC was 35% and 25% to the initial TSS concentration of river water where the final concentration of TSS obtained was 20 mg/L and 15.5 mg/L with percent TSS removal of 86.67% and 89.6 %. Keywords: Total Suspended Solid, Coagulation, Aluminium Sulfate, Poly Aluminium Chloride (PAC)